Subfoveal choroidal thickness and retinal nerve fiber layer alterations in chronic heart failure patients - (:unkn) unknown (CONSEL BRASIL OFTALMOLOGIA, 2021)
Purpose: To comparatively evaluate the subfoveal choroidal thickness and the peripapillaiy retinal nerve fiber layer thickness in patients with chronic heart failure relative to control subjects. Methods: A total of 72 chronic heart failure patients and 40 healthy control subjects were enrolled in this study. The patients were categorized into 2 groups: group 1: patients with 30-50% left ventricle ejection fraction and group 2: patients with the corresponding fraction value of <30%. The subfoveal choroidal thickness and the peripapillary retinal nerve fiber layer thickness were measured by spectral domain-optical coherence tomography. Results: The mean subfoveal choroidal thickness was 250.24 +/- 68.34 mu m in group 1 and 216.72 +/- 71.24 mu m in group 2, while it was 273.64 +/- 77.68 mu m in the control group. The differences among the 3 groups were statistically significant. The average peripapillary retinal nerve fiber layer thicknesses were 100.34 +/- 8.24, 95.44 +/- 6.67, and 102.34 +/- 8.24 mu m, respectively. No significant differences were noted in the peripapillary retinal nerve fiber layer thicknesses between group 1 and control group, but it was significantly lower in group 2. Conclusion: Our study thus revealed that the subfoveal choroidal thickness was lower in patients belonging to both the chronic heartfailure groups in comparison to those in the control group. However, the alteration in the peripapillary retinal nerve fiber layer thickness was noted in only patients with <30% left ventricle ejection fraction. In the clinical practice, reductions in these values are correlated with decreased left ventricle ejection fraction, which may be important for the follow-up of chorioretinal diseases and the evaluation of glaucoma risks in patients with chronic heart failures.
Keywords: Heart failure/complications; Choroid/pathology; Tomography, optical coherence; Nerve fibers; Retina; CEREBRAL-BLOOD-FLOW; CHORIOCAPILLARIS; DEGENERATION; ASSOCIATION; DISEASE